Concurrent validation of the MABC-2 and developmental coordination disorder questionnaire-BR - Montoro A.P.P.N.* (2016)
Introduction: The Movement Assessment Battery for Children, Second Edition (MABC-2) has been widely used in national literature for the diagnosis of Developmental Coordination Disorder (DCD). The relationship of MABC-2 with the scientifi c gold standard instrument for DCD, the Brazilian version of the Developmental Coordination Disorder Questionnaire (DCDQ-BR), is not well established and is rather controversial. Objective: The aim of this study was to verify the concurrent validity of the MABC-2 motor battery and the DCDQ-BR, controlled for sex and age group. Methods: The concurrent validation process took place with the participation of 350 schoolchildren aged 7-11 years from the cities of Florianopolis-SC and Manaus-AM and their parents or guardians. The agreement between instruments was assessed with the Spearman correlation test and simple linear regression using SPSS software version 20.0. Results: Positive correlation between instruments' scales was found. Conclusion: This study showed evidence of concurrent validity between MABC-2 and DCDQ-BR, suggesting that MABC-2 can be used as an indicator for developmental coordination disorder.